Research projects as a driving force for open source development and a fast route to market: RODA, SCAPE and E-ARK - a case study - Silva, Hélder (2014)
Research projects, specially in the computer science domain, have consistently provided outputs as open source products or updates to long-standing open source projects. This occurs due to the shared openness nature of both research and open source, that enables re-use by the community spanning new developments in both research and open source products. But when an open source project serves a community and a real-world problem, the impetuousity of research can clash with the inertia of real-world application. Nevertheless, research projects can bring the much needed innovation to open source projects, and open source projects can bring the much needed route to market that research funders look for the outputs of the research they fund, ensuring the budget spent in research actually reaches the community and improves the world. This paper presents an analysis of this dynamic with a case study about RODA, an open source repository for digital preservation, used in memory institutions such as archives, and two research projects, SCAPE, focused on digital preservation scalable services, and E-ARK, focused on standardization of information packages, integration with real-world applications, and database preservation. The paper further tries to identify good practices for using existing open source projects in research and assure that research outputs are further carried into main versions of open source projects and find their way to the final user.